2012
DOI: 10.1345/aph.1r497
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Dosing to Reverse Warfarin Based on INR, Route of Administration, and Home Warfarin Dose in the Acute/Critical Care Setting

Abstract: Vitamin K dose, route, and initial INR influence subsequent INR values. INR reduction is similar for intravenous vitamin K doses of 2 mg or greater. Preadministration of FFP does not alter INR values at 48 hours or more after vitamin K administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 19 publications
2
46
2
1
Order By: Relevance
“…17 The current data also suggest that different doses and routes of vitamin K have similar efficacy and safety. These findings differ from those in a retrospective chart review by Tsu and others, 8 who concluded that IV administration of vitamin K was associated with a more rapid decrease in INR than oral administration in a population of hospitalized patients. However, the patients who received oral vitamin K had higher mean baseline INR than those who received IV vitamin K (5.67 versus 5.09), and the mean decreases in INR at 24 h after the intervention were similar for the IV and oral routes (3.55 and 3.53, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…17 The current data also suggest that different doses and routes of vitamin K have similar efficacy and safety. These findings differ from those in a retrospective chart review by Tsu and others, 8 who concluded that IV administration of vitamin K was associated with a more rapid decrease in INR than oral administration in a population of hospitalized patients. However, the patients who received oral vitamin K had higher mean baseline INR than those who received IV vitamin K (5.67 versus 5.09), and the mean decreases in INR at 24 h after the intervention were similar for the IV and oral routes (3.55 and 3.53, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the patients who received oral vitamin K had higher mean baseline INR than those who received IV vitamin K (5.67 versus 5.09), and the mean decreases in INR at 24 h after the intervention were similar for the IV and oral routes (3.55 and 3.53, respectively). 8 Consistent with our results, the incidence and duration of bridging anticoagulation, rate of thromboembolism, and 30-day mortality rate were not significantly different between the IV and oral administration groups. 8 However, for reasons that the authors stated were unclear to them, hospital length of stay was significantly longer among patients who received vitamin K by the IV route than among those who received vitamin K by the oral route (13.54 versus 10.16 days, p = 0.02).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…route causes a reduction in the INR within the first six to eight hours after administration. 4 However, the reduction in INR achieved after a 24-to 48-hour period is similar with the i.v. and oral routes.…”
Section: Warfarin Reversal Optionsmentioning
confidence: 51%
“…phytonadione dose. 4 These shortacting agents have a faster onset of action than i.v. phytonadione because of the time required for formation of vitamin K-dependent clotting factors with phytonadione.…”
Section: S14mentioning
confidence: 99%